Influence of neck circumference, waist circumference and body mass index among children with overweight and normal weight - Berni, Andrea (2021)
ABSTRACT OBJECTIVE: To compare the measurements of neck circumference, waist circumference, and body mass index (BMI) between obese and eutrophic children. METHODS: Cross-sectional research, using primary and case control data, with a comparative approach of anthropometric variables, carried out with 218 students, 119 girls and 99 boys, from a municipal elementary school in São Paulo. Data collected were sex, age, body weight, height, neck circumference (NC), and waist circumference (WC). The BMI was calculated and classified using the BMI growth curve, according to age, in percentiles. For data analysis, non-parametric tests were applied. RESULTS: According to the BMI, 36.2% of the children were overweight when the agreement test was performed between all physical circumference measurements. However, there was a weaker agreement between BMI and NC and between BMI and WC measures. The correlation between the measures was greater between BMI and WC (62%), compared to between BMI and WC and between NC and WC. CONCLUSION: The use of the NC measure, as an additional measure for anthropometric assessment in pediatric patients, is suggested, due to its practicality and as a complement for screening and monitoring childhood obesity.   DESCRIPTORS: Circumference, Anthropometry, Child, Obesity. RESUMO OBJETIVO: Comparar as medidas de circunferência do pescoço, circunferência da cintura e índice de massa corporal (IMC) entre crianças com obesidade e eutróficas. MÉTODOS: Pesquisa do tipo transversal, por meio da coleta de dados primários e caso controle, com abordagem comparativa das variáveis antropométricas, realizada com 218 escolares, 119 meninas e 99 meninos, de uma escola municipal de ensino fundamental em São Paulo. Foram coletados dados como: gênero, idade, peso corporal, estatura, circunferência do pescoço (CP) e circunferência da cintura (CC), calculado e classificado o IMC pela curva de crescimento IMC por idade em percentil. Para análise dos dados foram aplicados testes não paramétricos. RESULTADOS: De acordo com o IMC, 36,2% das crianças apresentavam excesso de peso; quando realizado o teste de concordância entre todas as medidas de circunferências físicas. No entanto, observou-se concordância mais fraca entre entre as medidas IMC e CP e entre IMC e CC. A correlação entre as medidas foi maior entre IMC e CC (62%), mostrando-se novamente mais fraca entre IMC e NC, bem como para CP e CC. CONCLUSÃO: O uso da medida da CP, como uma medida adicional para avaliação antropométrica do grupo pediátrico é sugerido, devido à sua praticidade e complementação para triagem e monitoramento da obesidade infantil. DESCRITORES: Circunferência, Antropometria, Criança, Obesidade.